Hubungan Kehamilan Usia Ibu Resiko Tinggi Dengan Perkembangan Emosi Anak Di Masa Golden Age (Usia 3-5 Tahun) Di Wilayah Kerja Puskesmas Rami Kota Pematangsiantar - Ringo, Kristiana Siringo; Pakpahan, Rosmega; Damanik, Oktavania (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Young pregnant women are at risk of experiencing stress or pressure that canaffect fetal growth and development. Purpose: This study aims to determinethe relationship between high-risk maternal age pregnancy and emotionaldevelopment of children during the Golden Age (ages 3-5 years) in the workingarea of Rami Health Center, Pemangtangsiantar City in 2020. Method: Thistype of research is observational with a historical cohort design. The populationwas all pregnant women in 2017-2019 who attended posyandu and were inthe working area of Rami Health Center, Pematangsiantar City. The number ofsamples used was 74 people obtained using purposive sampling technique. Thedata analysis technique used chi square. Result: The results showed that there was a significant relationship between income and children’s emotionaldevelopment, p value 0.01 RR = 5,806 (95% CI 1.381 24,406). There is asignificant relationship between maternal age at pregnancy and emotionaldevelopment of children aged 3-5 years with a p value of 0.037, RR=3,33 (95%CI 1.997 11,145). Conclusion: It is recommended that the puskesmas provideeducation about the importance of paying attention to the age of the motherwhen pregnant and unmarried at a young age or if married at a young age candelay pregnancy until adulthood from 20-35 years.